Strategie finansowania działalności spółek giełdowych z sektora agrobiznesu – wyniki badania opinii zarządzających - Zabolotnyy, Serhiy (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
In the article the opinions of agribusiness joint stock companies’ managers concerning strategies of financing are presented. By means of survey technique the hierarchy of sources of financing, factors influencing the capital structure and methods of equity capital estimation were defined. It was stated that in the companies of agribusiness variable strategies of capital management were applied, with the advantage of moderate strategies. The most effective source of financing was long-term debt. The main reason for increasing the debt level was the necessity to finance new investment projects. Among the most important factors determining the choice between long-term and short-term debt were the necessity to synchronize the term of debt with the period of current assets’ cycle as well as the lower interest rate of the short-term debt comparing to long-term debt.